Influence of metal ion crosslinking on the nanostructures, stiffness, and biofunctions of bioactive peptide hydrogels. Issue 10 (19th July 2022) - Mohammed, Mohiuddin; Chakravarthy, Rajan Deepan; Lin, Hsin-Chieh
Abstract : Mg 2+ induced peptide hydrogels exhibit tunable stiffness, nanostructures and self-assembly of hMSC into multicellular spheroids. Abstract : Self-assembled peptide hydrogels have a wide range of biomedical applications since they lack toxic crosslinkers and contain fibrillar structures resembling an extracellular matrix (ECM). Despite the advances, it remains challenging to achieve the self-assembly of well-defined nanostructures for controlled specific cell functions of stem cells. Here, we demonstrated the self-assembly of pentapeptide Phe-Phe-Arg-Gly-Asp (FFRGD) N-capped with a fluorinated benzyl group that forms stable supramolecular hydrogels with a twisted nanobelt morphology at physiological pH. The addition of magnesium (Mg 2+ ) metal ions stimulates the formation of hydrogels (1a ) with a twisted nanofibril network with enhanced mechanical properties, exhibiting a storage modulus of 3.6 kPa. Hydrogel (1b ) triggered by calcium (Ca 2+ ) metal ions proceeded through strong metal–ligand chelation with a nanofibrous morphology of high cross-linking density, showing an increased storage modulus of 47 kPa. However, in the presence of barium (Ba 2+ ) ions, the hydrogels (1c ) displayed weaker mechanical properties with a gel modulus of 0.69 kPa due to poor metal–ligand cross-linking. The resulting hydrogels exhibited a loosely cross-linked twisted nanobelt morphology. All hydrogelators exhibited excellent biocompatibility on two different cell lines, namely, human mesenchymal stem cells (3A6-RFP) and mouse fibroblasts (L929). We also study the multicellular self-assembly of hMSC within a hydrogel matrix using a 3D culture, and the results are highly dependent on the mechanical stiffness of the scaffold support. The cell culture results of Mg 2+ induced FFRGD hydrogels showed multiple cell aggregates similar to MSCs on Matrigel, while Ca 2+ or Ba 2+ induced hydrogels showed highly dispersed cells with smaller cellular spheroids, characteristic of 3A6-RFP cells. Overall this work provides a simple approach for fabricating bioactive peptide hydrogels with tunable mechanical stiffness and biological functions.